Memorandum of Understanding between the James P. Grant School of Public Health, BRAC University, Dhaka, Bangladesh and London School of Hygiene and Tropical Medicine, University of London, United Kingdom (2004) - James P. Grant School of Public Health, BRAC University; London School of Hygiene and Tropical Medicine, University of London (James P. Grant School of Public Health and London School of Hygiene and Tropical Medicine, 2013)
The James P. Grant School of Public Health, BRAC University, is registered in Dhaka, Bangladesh under the Private University Act of 1993. Hence forth it is referred to as the JPG-SPH-BU. The London School of Hygiene and Tropical Medicine, University of London, Henceforth it is referred to as the LSHTM. JPG-SPH-BU and LSHTM are committed to this joint endeavour, but recognise that the envisioned activities are subject to the availability of resources, as mutually agreed upon. Both JPG-SPH-BU and LSHTM will endeavour to mobilise the needed resources from their respective institutions, as well as from other external sources.